2020
DOI: 10.2147/ndt.s247599
|View full text |Cite
|
Sign up to set email alerts
|

<p>Protective Effects of <em>Spirulina platensis</em>, Voluntary Exercise and Environmental Interventions Against Adolescent Stress-Induced Anxiety and Depressive-Like Symptoms, Oxidative Stress and Alterations of BDNF and 5HT-3 Receptors of the Prefrontal Cortex in Female Rats</p>

Abstract: Background and Purpose Ample evidence indicates that chronic adolescence stress is associated with an increased risk of developing neuropsychiatric disorders in adulthood. Given the importance of the effective therapeutic ways to overcome adolescent stress-related deficits, the present study investigated the effects of Spirulina platensis (SP), environmental enrichment (EE), and voluntary exercise (EX) and their combination on anxiety or depression-like behaviors, oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 97 publications
(131 reference statements)
2
11
0
Order By: Relevance
“…The results for the effects of stress on depression are in line with previous studies that showed stress could induce depression and anxiety [8,21,22]. Stress increases depression and anxiety via increased levels of corticosterone [1,18]. Importantly, our findings showed that sake yeast alleviated the effects of stress.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results for the effects of stress on depression are in line with previous studies that showed stress could induce depression and anxiety [8,21,22]. Stress increases depression and anxiety via increased levels of corticosterone [1,18]. Importantly, our findings showed that sake yeast alleviated the effects of stress.…”
Section: Discussionsupporting
confidence: 91%
“…The OFT was conducted to assess anxiety as reported by others [1]. Briefly, behavioral responses in time were investigated in a dark area (72×72×45 cm) for 20 minutes.…”
Section: Open-field Test (Oft)mentioning
confidence: 99%
See 1 more Smart Citation
“…[90] It has been reported that neuronal damage due to chronic oxidative stress and inflammation leads to a reduction in prefrontal cortex size and dysfunction in the production of neurotransmitters in depressed patients. [91][92][93] There are many pieces of evidence that brain serotonin dysfunction plays an essential role in developing cardiac abnormalities via vasoconstriction and inflammation. [15,16,94] In the present study, RA (25 and 50 mg/kg) increased serotonin levels relative to the CUS-control group.…”
Section: Discussionmentioning
confidence: 99%
“…Stress in adolescence is associated with enhanced anxiety levels and depression in adulthood, as well as elevated oxidative stress markers. Environmental enrichment, exercise, and treatment with Spirulina platensis tend to reduce oxidative damage induced by stress [ 106 ].…”
Section: Oxidative Stress Biomarkers and Pediatric Depressive Disordermentioning
confidence: 99%